Positive Psychology-Based Counselling Intervention to Reduce Academic Procrastination Among Guidance and Counselling Students - Ainur Rosidah; Eko Susanto; Arman (Universitas PGRI Yogyakarta, 2025)
Academic procrastination hurts students’ academic performance and emotional well-being. Addressing this issue is essential in higher education settings. This study examines the effectiveness of positive psychology-based counselling in reducing academic procrastination among guidance and counselling students. This study involved 16 students from Muhammadiyah University of Pringsewu, Indonesia, who used the Pure Procrastination Scale (PPS) to measure their levels of procrastination. A pretest-posttest control group design was applied. The experimental group received a positive psychology intervention consisting of 8 weekly sessions, while the control group participated in conventional group counselling. Data were analyzed using an independent t-test, which showed a significant difference between the two groups after the intervention (p = 0.001), with a strong effect size (Cohen’s d = 2.46). Furthermore, the intervention increased conscientiousness, self-restraint, and self-control, all of which are important for academic discipline. These results indicate that positive psychology-based counselling is effective in reducing academic procrastination and enhancing students' self-regulation skills. Keywords: academic procrastination, positive psychology-based counseling, conscientiousness, self-restraint, self-control